2019
DOI: 10.3389/fbioe.2019.00321
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fibronectin Knockout on Proliferation and Differentiation of Human Infrapatellar Fat Pad-Derived Stem Cells

Abstract: Fibronectin plays an essential role in tissue development and regeneration. However, the effects of fibronectin knockout (FN1-KO) on stem cells' proliferation and differentiation remain unknown. In this study, CRISPR/Cas9 generated FN1-KO in human infrapatellar fat pad-derived stem cells (IPFSCs) was evaluated for proliferation ability including cell cycle and surface markers as well as stemness gene expression and for differentiation capacity including chondrogenic and adipogenic differentiation. High passage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…FN1 plays an important role in tissue development and regeneration. Wang et al [62] found that the fat pad stem cells’ cartilage differentiation and fat differentiation ability decreased significantly after knocking out FN1. Gcm1 transcription factor covering FGF signal can promote the terminal differentiation of trophoblast stem cells [63] , in addition, the gene can guide the change of cell fate by activating the glial development program in the multipotent precursor cells of the nervous system [64] .…”
Section: Real Data Analysismentioning
confidence: 99%
“…FN1 plays an important role in tissue development and regeneration. Wang et al [62] found that the fat pad stem cells’ cartilage differentiation and fat differentiation ability decreased significantly after knocking out FN1. Gcm1 transcription factor covering FGF signal can promote the terminal differentiation of trophoblast stem cells [63] , in addition, the gene can guide the change of cell fate by activating the glial development program in the multipotent precursor cells of the nervous system [64] .…”
Section: Real Data Analysismentioning
confidence: 99%
“…In addition, FN1 exhibits chemotactic activity and attracts monocytes, and is involves in both blood coagulation and wound healing (11). FN1-knockout Fibronectin 1 inhibits the apoptosis of human trophoblasts by activating the PI3K/Akt signaling pathway mice have an embryonic lethal phenotype that is characterized by severe cardiac and vascular disorders (15), indicating that FN1 is essential for embryonic development. As FN1 is highly expressed in tumor vessels and mediates angiogenesis during tumorigenesis, it also plays important roles in cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Fibronectin (FN), one of the main brillary proteins, has been involved in cell-multitrophic (celldifferentiating) and cellular proliferation and differentiation. Following FN1-KO extension, the number of human infrapatellar fat pad derived stem cells was increased, but this rise was negated by FN1 cells after implantation into ECM [23]. Likewise, recent ndings have found that the glucocorticoid receptor enhances the proliferative mesenchymal progenitor cell's acquisition of broblast matrix-derived signals such as Fn1 through and Wnt-1 and JAK-STAT, concerning their activity in the extracellular environment by other cells, and thus indirectly regulates a subset of those cells responsible for promoting tissue extracellular matrix gene expression, especially the cells [24].…”
Section: Discussionmentioning
confidence: 99%